2011
DOI: 10.1289/ehp.1002922
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Polychlorinated Biphenyls in Relation to in Vitro Fertilization Outcomes

Abstract: Background: Human exposure to polychlorinated biphenyls (PCBs) remains widespread. PCBs have been associated with adverse reproductive health outcomes including reduced fecundability and increased risk of pregnancy loss, although the human data remain largely inconclusive.Objective: Our goal was to explore the relationship between serum PCB concentrations and early pregnancy loss among a large cohort of women undergoing in vitro fertilization (IVF) between 1994 and 2003.Methods: Concentrations of 57 PCB congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 81 publications
2
41
0
Order By: Relevance
“…When improperly stored or disposed of, PCBs entered the environment in soil, water, and air, and were subsequently incorporated into the food chain. Although banned in 1979 (McFarland and Clarke, 1989), nearly all humans and wildlife have measurable amounts of PCBs in their bodies (Meeker et al, 2011; Quinn et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…When improperly stored or disposed of, PCBs entered the environment in soil, water, and air, and were subsequently incorporated into the food chain. Although banned in 1979 (McFarland and Clarke, 1989), nearly all humans and wildlife have measurable amounts of PCBs in their bodies (Meeker et al, 2011; Quinn et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The fact that cellular NL levels were similar between our experimental conditions is most probably at the origin of the identical accumulation of PCBs within adipocytes. While PCB concentrations in the culture medium were in the same range than those measured in the human serum [29], [30], the PCB levels found in cultured adipocytes after 12 hours of incubation (data from Table 1 are equivalent ∼175 ng PCB congeners per mg NLs) were much higher than those measured in vivo , in the human adipose tissue (from 0.02 to 0.66 ng total PCBs per mg lipids) [34][38]. It reflects a high propensity of differentiated rat adipocytes to store PCBs [4].…”
Section: Discussionmentioning
confidence: 75%
“…The PCBs were added to the culture medium as ethanolic solution and four conditions of PCB contamination were tested: ( i ) 2,4,4′-trichlorobiphenyl (PCB-28); ( ii ) 2,3′,4,4′,5-pentachlorobiphenyl (PCB-118); ( iii ) 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB-153); ( iv ) an equimolar mixture of three PCB congeners (PCB-28, -118 and -153), also called cocktail of PCBs. In all conditions of contamination, each PCB was added to the culture medium at a concentration of 300 nM, which is within the range of concentrations found in in vivo and in vitro studies [4], [29], [30]. Impact of the ethanol vehicle was tested earlier [4].…”
Section: Methodsmentioning
confidence: 99%
“…Maternal serum PCB concentrations have been documented during critical windows of development, including the periconception interval and early pregnancy [104], and PCB levels are detectable within human follicular fluid [105,106]. More recently, follicular fluid and serum PCBs have been associated with reduced oocyte fertilization [107] and with reduced embryo implantation during IVF [108], although a systematic review concluded that the epidemiologic evidence to date is insufficient to support a causal association [109].…”
Section: Exposure To Polychlorinated Biphenylsmentioning
confidence: 99%